(untitled) (Innovative professional education, 2025)
The article examines the problem of professional self-determination of students of vocational (vocational-technical) and professional higher education, which is an important factor in their competitiveness in the labor market. The criteria for assessing the socio-pedagogical effectiveness of career guidance work and their impact on the formation of strategies for the professional development of young people are considered. Quantitative and qualitative indicators of the effectiveness of career guidance activities that contribute to raising awareness and consciousness of career choice are analyzed. The obtained results can be used to improve the system of vocational guidance and increase its effectiveness in the current socio-economic conditions.